Pengaruh Partisipasi Anggota Terhadap Keberhasilan Koperasi Simpan Pinjam di Kecamatan Buleleng - Tiara, Lisa; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research aims to determine the effect of member participation on the success of savings and loan cooperatives in Buleleng District. This research uses a causal quantitative design. In this research, the population used was all members of savings and loan cooperatives in Buleleng District. The sample was determined using proportional techniques and the Slovin formula, so that a sample of 197 was obtained. This research used quantitative data using primary data sources obtained through questionnaires and secondary data obtained from the Buleleng Regency Trade, Industry, and UKM Cooperative Service. The data collection method uses questionnaires that are distributed directly to members of active savings and credit cooperatives in Buleleng District using Likert scale measurements. The data collection method also uses documentation and observation. The data analysis technique used is simple linear regression analysis with partial hypothesis testing (t-test). The results of this research indicate that there is a relationship between member participation and the success of savings and loan cooperatives in Buleleng District and also that member participation has a positive and significant effect on the success of savings and loan cooperatives in Buleleng District.